Good growing : why organic farming works - Duram, Leslie A. (Our sustainable future, 2005)
"This book explains why organic production and consumption have seen such phenomenal growth in recent years - and, even more important, why they should. A clear-eyed, close-up look at the compelling reasons for organic farming and the methods that make it work, Good Growing begins with a frank account of the problems with conventional industrial agriculture - the pesticide use, pollution, and corporate control that have undermined public health and devastated rural towns and family farms."--Jacket